The impact of AI technology on sustainability in the e-commerce industry - Feng Wang Bing (2024)
In the context of today's digital global economy, the e-commerce industry has gradually become an essential part of modern business activities due to its convenience and efficiency.However, the rapid development of the e-commerce industry has brought about a series of challenges, including how to achieve sustainability.At the same time, the widespread application of artificial intelligence (AI) technology has brought new possibilities and opportunities to the e-commerce industry.Therefore, the main objective of this research is to systematically explore and understand the deep mechanisms of the impact of AI technology on the sustainability of the e-commerce industry. This research sets four specific research questions.Firstly, we will clarify the forms and characteristics of AI applications in the e-commerce industry.Currently, while AI's application in the e-commerce industry is becoming more widespread, its specific forms and characteristics have not been thoroughly studied and summarized.Secondly, we will delve into the mechanisms and pathways through which AI affects the sustainability of e-commerce enterprises.Although some studies have suggested that AI may have an impact on the sustainability of e-commerce enterprises, the specific mechanisms and pathways of this impact are not yet clear. Once again, we will reveal whether there are differences in the performance of artificial intelligence technology on the sustainable impact of different types of e-commerce enterprises, and how these differences arise. We need to construct a scientific empirical model for research to quantitatively verify the sustainable impact of artificial intelligence on e-commerce enterprises. To achieve these goals, the study will cite literature and use statistical methods such as multiple linear regression to construct empirical research models, and validate the proposed hypotheses. Through verification, this study provides scientific basis for strategic decision-making and policy formulation of e-commerce enterprises, and will provide theoretical guidance for the application of artificial intelligence in the e-commerce industry. This research innovation lies in elucidating the impact mechanism of artificial intelligence technology on the sustainability of e-commerce, providing a more in-depth theoretical basis and significant practical impact on the sustainable development of e-commerce, and providing valuable experience for the exploration and development of its industry.